Avaliação da compactação de cromatina durante a maturação epididimária do espermatozoide de touro - Martins, Muller Carrara (2018)
The current andrological exams evaluate the concentration, vigor, motility, swirling and morphological pathologies of spermatozoa. However, even when approved for andrological examinations, some bulls do not respond effectively, either in natural mating or in vitro fertilization processes. Alterations in the sperm chromatin can be a factor that influence the performance of bulls and is usually not evaluate in andrological exams. This study aims to evaluate the condensation of chromatin during sperm maturation in the epididymis, correlating morphometric characteristics of spermatozoa, chromatin condensation and epididymal maturation. For this, spermatozoa were collected from the seminiferous tubule, head, body and tail of the epididymis, as well as the ductus deferens of five bulls. These spermatozoa were evaluated by computational image analysis of toluidine blue stained smears. In general, spermatozoa of the seminiferous tubule presented smaller area, perimeter, width, length, ellipticity, and Fourier harmonics (F0, F1 and F2) when compared to the epididymis (head, body and tail) and ductus deferens. The analysis of decondensation and heterogeneity of chromatin showed that both parameters decreased during the process of sperm maturation. The proportion of normal spermatozoa (with absence of chromatin decondensation areas) was lower in the seminiferous tubules in relation to the other regions. In addition, superior percentage of spermatozoa with chromatin decondensation in the base (DB), basal half (DBH) and central axis (DCA) of the head was observed in the seminiferous tubules when compared to the other analyzed regions. The type of chromatin decondensation influences morphometric parameters of the spermatozoa head. Heads that possess total decondensation have smaller area when evaluated by two-dimensional image analysis, conversely, heads with disperse decondensation have a larger area. Heads with larger decondensation tend to be spherical, with greater volume, but with smaller area when observed two-dimensionally, and those with dsipersed decondensation are quite flattened, with smaller volume, but larger area. During sperm maturation, the spermatozoa initially present total chromatin decondensation. Then, the lateral borders begin the condensation process, followed by condensation of the apical region, central region, and the basal region of the head, respectively. Therefore, it has been demonstrated that epididymal maturation is important for the chromatin condensation, consequently, for the final morphology of the spermatozoa.